Electron Impact Ionization of Ethylene Glycol Molecule - Mykyta, M.I.; Romanova, L.G.; Zavilopulo, A.N.; Shpenik, O.B. (Ukrainian Journal of Physics, 2022)
Mass spectrometric studies of the positive ion yield due to the electron impact ionization of ethylene glycol molecules in the gas phase have been carried out. The ionization energy of a molecule and the energies of appearance of basic fragment ions have been obtained based on the ionization efficiency curves. The value of the ionization energy for a С2H6O2 molecule has been determined experimentally to be (10.21 ± 0.25) eV. The experimental values of the energies of appearance for the basic fragment ions with m/z = 31, 33, and 29 have been found to be (11.13 ± 0.25), (10.56 ± 0.25), and (17.79 ± 0.25) eV, respectively.